2011
DOI: 10.2136/vzj2009.0138
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Porosity and Saturated Hydraulic Conductivity of Binary Mixtures

Abstract: Gravels and coarse sands make up significant portions of some environmentally important sediments, while the hydraulic properties of the sediments are typically obtained in the laboratory using only the fine fraction (e.g., <2 mm or 4.75 mm). Researchers have found that the content of gravel has significant impacts on the hydraulic properties of the bulk soils. Under the study reported here, Laboratory experiments were conducted to measure the porosity and the saturated hydraulic conductivity of binary mixture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
65
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 27 publications
1
65
0
Order By: Relevance
“…However, gravel content also has a significant impact on the soil porosity and hydraulic properties (Zhang et al 2011). It is hard to simulate the soil moisture state accurately in land models that neglect gravel, especially when the actual soil gravel content is large.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…However, gravel content also has a significant impact on the soil porosity and hydraulic properties (Zhang et al 2011). It is hard to simulate the soil moisture state accurately in land models that neglect gravel, especially when the actual soil gravel content is large.…”
Section: Theorymentioning
confidence: 99%
“…Zhang et al (2011) conducted an experiment with a mixture of glass beads and fine soil and showed that the porosity of the mixture decreased linearly to a minimum value and then increased as the gravel fraction increased. However, several reports have noted that gravel cannot be neglected in calculating the amount of soil water retention, due to the fact that the pore structure of weathered gravel in particular is conducive to holding water (Ma and Shao 2008;Ravina and Magier 1984).…”
Section: Introductionmentioning
confidence: 99%
“…In summary, the interparticle forces determine soil pore conditions, and the interparticle forces depend on soil surface charges, electrolyte concentration and cationic polarization of the adsorbed counterions. In addition, particle‐size distribution is also an important factor affecting soil porosity (Wu et al ., ; Hwang & Choi, ; Zhang et al ., ; Sakaki & Smits, ). Therefore, soil water movement depends in a complex way on the interrelations between soil surface charges, electrolyte concentration, ionic polarization and particle‐size distribution.…”
Section: Introductionmentioning
confidence: 98%
“…(Barr, 2001;Bernabé et al, 2004;Dias et al, 2004;Dunning, 2005;Jarvis et al, 2002;Kamann et al, 2007;Morin, 2006;Morris and Johnson, 1967;Sperry and Peirce, 1995;Zhang et al, 2011). A similar type of analysis uses binary mixtures in laboratory experiments.…”
Section: Introductionmentioning
confidence: 99%
“…However it has been pointed out that the weak point of this method is the inability to duplicate ideal packing of large and small sediments, not to mention the infinite combinations. Research by Zhang et al (2011) based on glass beads to simulate sediments reassured us that results from laboratory testing either overestimate or underestimate effective porosity.…”
Section: Introductionmentioning
confidence: 99%